May Measurement Month 2017: an analysis of blood pressure screening in Sudan—Northern Africa and Middle East. (24th April 2019) - Ali, Ibtisam; Behairy, Hind; Abugroun, Ashraf; Beaney, Thomas; Kobeissi, Elsa; Abdalla, Asma; Mohamed, Abdelrahim; Wagialla, Naiema; Medani, Safa S; Ismail, Elamin M; Hassan, D A; Altahir, Fatima; et al.
Abstract: Elevated blood pressure (BP) is a growing burden worldwide, leading to over 10 million deaths each year. Sudan has the second highest prevalence of hypertension in North Africa. One in four people with a non-communicable disease has hypertension. May Measurement Month (MMM) is a global initiative, aimed at raising awareness of high BP to act as a temporary solution to the lack of screening programs worldwide. The MMM screening survey provided an opportunity to correlate between unique risk factors and BP levels among Sudanese population. Such an approach allows for directing efforts towards setting the appropriate preventive measures as opposed to disease treatment. An opportunistic cross-sectional survey of volunteers aged ≥18 was carried out in May 2017. Blood pressure measurement, the definition of hypertension and statistical analysis followed the standard MMM protocol. The study was conducted at 100 sites distributed in four states: Khartoum, Gezira, Blue Nile, and Kassala. Overall, a total of 44 413 participants were enrolled in the survey. After imputation, 7332 out of 44 118 participants with an available mean of the second and third readings had hypertension (16.6%). A total of 6956 (15.9%) participants were found to have hypertension of the 43 742 who were not receiving treatment. Among participants who were on treatment, 155 out of 374 (41.3%) had uncontrolled BP. After adjusting for age and sex, systolic and diastolic BP's were significantly higher in those receiving antihypertensive treatment, with a previous history of stroke and with elevated body mass index. Systolic BP was significantly higher in people with diabetes and with previous myocardial infarction. Smoking was associated with increased diastolic BP and decreased systolic BP. Alcohol intake as well as BP measurement on left vs. right arm had no association with BP reading. The MMM17 was the largest BP screening campaign ever held in the country. A considerable percentage of detected hypertensives were not on treatment with a significant proportion of uncontrolled hypertension among those on treatment. These results suggest that opportunistic screening can identify significant numbers with raised BP.